HOW DEPARTEMENT OF TOURISM AND CULTURE, YOUTH AND SPORT SERVICES MANAGES TOURISM OBJECT IN KARANGNYAR - KIRNAWATI, DIYAH; ANNANINGTYAS, CUCUT (RADIANT: Journal of Applied, Social, and Education Studies, 2020)
The natural beauty with all its potential beauty has to be kept, preserved, and developed by Karanganyar official tourism management. Cultural diversity, people hospitality and historical values of Karanganyar become tourist main attraction and wonders. This research aims at finding the activities of the Karanganyar Tourism, Youth and Sports Service which are regularly managed by the Karanganyar Tourism, Youth and Sports Service. The research use method triangulation such as document analysis, interview and observation. Data from document analysis as from some books, Observation had been done when giving some questions to the officer in the office and the writer’s experiences internship for 3 month. The benefits of the study for students is that they can obtain knowledge from result through which is presented and through a new experience. For Government, it can support Department of tourism and culture, Youth and Sport Services Karanganyar with good regulation. The government has gived regulation likes give infrastructure tourism object in Karanganyar not only Department of tourism and culture, Youth and Sport Services Karanganyar but just to society.